PENGARUH KOMPETENSI GURU TERHADAP KETRAMPILAN MENGAJAR GURU - Ulya Zain Hayoto (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the extent to which teacher competence influences teachers' teaching skills. Data collection techniques in this research are questionnaires and documentation. The results of this research are that it has a positive influence on teachers' teaching skills. There is an influence between teacher competence and teacher teaching skills. There is an influence between teacher competence and teacher teaching skills as seen from the results of data analysis which has been carried out using the multiple linear regression formula which produces a regression equation model (y = 34.545 + 32.4 x1 - 3.11 x2), showing that the F-calculation value when compared with the F-table, it turns out to be much larger, namely F-count = 47.722 through the significance test and 0.14 in the F test. Meanwhile, the F-table with a dk in the numerator of 2 and a dk in the denominator of 20 shows values ​​of 3.49 and 5.85 . This shows that the regression model is very significant. Means the hypothesis (Ha) that the author proposes in this research.